Lemon Grass: A Review Article Depicting Its Extraction And Properties (Journal of Pharmaceutical Negative Results, 2023)
Cymbopogon citratus belonging to the family Gramineae is an herb worldwide known as lemongrass. The prefix lemon owes to its typical lemon like odour, due to presence of citral a cyclic monoterpene. Lemongrass has phytoconstituents such as tannins, flavanoids, alkaloids, and various essential oils in this herb. Secondary active metabolites of a number of components have also been implicated in the varied pharmalogical effects of this plant. The name Cymbopogon comes from the Greek word "kymbe –pogon," which means "boat-beard". Cymbopogon citratus, a perennial fragrant grass native to South India and Sri Lanka, is now widely grown throughout tropical America and Asia. The essential oil is extracted from freshly cut and slightly dried leaves, which are used medicinally, Pharmacological properties of Cymbopogon citratus are extensively explored, however, research suggests that other species may prove helpful pharmaceutically. This review aims to discuss various aspects of lemongrass oil in respect of its properties and extractive procedure along with it identification methods. Lemon grass tea contains several biocompounds in its decoction, infusion and essential oil extracts. Anti-oxidant, anti-inflammatory, anti-bacterial, anti-obesity, antinociceptive, anxiolytic and antihypertensive evidences of lemongrass tea were clearly elucidated to support initial pharmacological claims. The compounds identified in Cymbopogon citratus are mainly terpenes, alcohols, ketones, aldehyde and esters. Some of the reported phytoconstituents are essential oils that contain Citral , Citral , Nerol Geraniol, Citronellal, Terpinolene, Geranyl acetate, Myrecene and Terpinol Methylheptenone. Appreciable activity was observed against various isolates of Candida and clinical isolates of Aspergillus fumigatus, Microsporum gypseum and Trichophyton mentagrophyte. Citral is a combination oftwo stereoisomeric monoterpene aldehydes; the trans isomer geranial is in predominance to the cis isomer neral.This paper reviews recent information on extraction methods of lemongrass essential oil, its chemical composition depending on the origin of the plant, bioactivity of the oil constituents as well as potential application as a food preservative.